2017
DOI: 10.1155/2017/3674140
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Hypothermia in Asphyxiated Neonates: Experience from Neonatal Intensive Care Unit of University Hospital of Marrakech

Abstract: Introduction Therapeutic hypothermia (TH) is now recommended for the treatment neonates with hypoxic-ischemic encephalopathy (HIE). This treatment protocol is applied in our department since June 2012. The aim of this study is to report the first experience with head cooling in asphyxiated neonates in Morocco. Patients and Methods Prospective study of newborns admitted for HIE from July 18, 2012, to May 15, 2014, in Neonatal Intensive Care Unit (NICU) of Mohamed VI University Hospital. The results were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Major shortcomings were identified in the representativeness of the data with only three papers scoring a star in this question. [47][48][49] Reports about neonatal mortality and developmental outcomes had better scores for case ascertainment than those where incidence of intrapartum-related NE was examined. About half of the reports had issues with incomplete follow-up, which might further bias the results.…”
Section: Bias Evaluation Of the Included Studiesmentioning
confidence: 99%
“…Major shortcomings were identified in the representativeness of the data with only three papers scoring a star in this question. [47][48][49] Reports about neonatal mortality and developmental outcomes had better scores for case ascertainment than those where incidence of intrapartum-related NE was examined. About half of the reports had issues with incomplete follow-up, which might further bias the results.…”
Section: Bias Evaluation Of the Included Studiesmentioning
confidence: 99%
“…Despite management in a Level 2 nursery with access to whole-body cooling machines, cranial ultrasound, amplitude electro-encephalogram (aEEG) monitoring, competency of treatment and personnel with expertise in managing patients with TH, our findings are similar to those of a study in Uganda where patients were followed up for at least 2 years and were managed outside a Level 3 nursery. The GMDS was also used as one of the developmental assessment tools [14]. Cooling infants at Level 2 has some limitations as monitoring is not as intense as in a Level 3 nursery because of the high nurse:patient ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reporting outcome at 18-24 months suggest that neonates with HIE managed with TH outside the NICU might have a severe outcome and so its use outside these settings is still experimental [14,15]. This study sought to determine the long-term (12 and 18-24 months) outcome in neonates with HIE managed with TH in a setting where their care was offered in a high-care unit, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Another web-based survey involving 288 paediatricians and neonatologists in South Africa reported that 76% of the respondents firmly believed therapeutic hypothermia would be beneficial and 46% had been already cooling encephalopathic neonates in their units [24]. Wide implementation of therapeutic hypothermia across neonatal units in Morocco was suggested based on the outcome data of a prospective study involving just 32 asphyxiated neonates in a tertiary hospital in Marakkech [25].…”
Section: Current Practice Of Therapeutic Hypothermia In India and Other Lmicmentioning
confidence: 99%